Augmented Reality Implementation In House Type Design Aplications With Unity 3D Based On Android In Griya Medan Marelan Housing - Robiatul Adawiyah (LPPM Universitas Al Washliyah Labuhanbatu, 2019)
Augmented Reality (AR) is an environment that incorporates 3D virtual objects into the real environment. This research will incorporate Augmented Reality (AR) technology into a marker. From the marker will be used as input, then this application will detect marker so that the type of 3D house in Griya Medan Marelan housing will appear just above the marker as if it looks real and display the existing furniture inside the house displayed through Android smartphone. The conclusion of this research is by using Augmented Reality (AR) application that can simplify Griya Medan Marelan management in doing promotion and simplify the buyer in determining the desired type of house by looking at the type of house in 3D and information from each type of Griya Marelan house and can change the user paradigm regarding other functions of the smartphone. Therefore, the need for new innovations is useful as an attractive media campaign